Policies, Laws and Strategies for Responding to Cyberterrorism in Thailand - Natthamon Petchkla; Sumonthip Chitsawang (Fakultas Hukum Universitas Mataram, 2022)
This article explains the policies and strategies currently used in Thailand for responding to terrorism. This study uses in-depth interviews with technicians and policy analysis experts in the area of cyber-attack, including more than 30 people in 15 governmental agencies. Specifically, the study begins by exploring the definition of cyberterrorism. Moreover, the study uses document research in both Thai and English and concludes that Thailand’s governmental agencies understand the concept of cyberterrorism and have already established policies and strategies for responding to it in the future.